Thalassemia Mutations in Lower Northern Part of Thailand - Choopayak, Chonnanit; Mirasenaa, Saisiri; Poodendaen, Chanasorn; Jiraviriyakul, Arunya; Sangarun, Kanok-on; Shimbhu, Dawan (Asian Health, Science and Technology Reports, 2005)
Thalassemia is one of the most serious genetically transmitted diseases creating health problems in many parts of Thailand including the lower North. Therefore, screening test for both alpha and beta globin gene mutations will be useful for a program of prevention and control of thalassemic disease. The screening test includes osmotic fragility (OF) test, dichlorophenol-indophenol (DCIP) test, quantitation of HbA2, HbE screening and PCR analysis. Five hundred blood samples were collected from a population living in Uttaradit, Phetchabun, and Phitsanulok. The results showed a high frequency of thalassemic disorders (40.4%) in this population and one major thalassemic disease (compound heterozygous HbE/β-thal). Among them, heterozygous Hemoglobin E (HbE trait) was found to be the most common in 133 subjects (26.6%) and alpha thalassemia 1, Southeast Asian type carriers (α-thal 1, SEA) (heterozygous α-thalassemia 1) in 39 subjects (7.8%). Homozygous HbE (Homo HbE) was found in 19 subjects (3.8%), whereas heterozygous beta thalassemia (β-thal trait) was found in 11 subjects (2.2%). In addition to HbE/β-thal, 6 more subjects with compound heterozygote were also found, 4 of α-thal 1/HbE, and 2 of α-thal 1/ β-thal. By using PCR, HbE mutation was confirmed and -thal traits were analyzed for 5 different mutations. Among 11 β-thal traits, mutation in codon 41/42 (4 bp deletion) was the most frequent in 9 samples (1.8%), codon 17 (A-T) mutation was detected in one sample (0.2%), IVS-1-5 (G-C) was detected in one sample (0.2%), whereas mutation in codon 71/72 (+A) and IVS-1-1 (G-T) was not detected. The data will be useful for setting a strategy for prevention and control of thalassemia in this area.